Perbaikan Manajemen Pergudangan pada PT. FSCM - Yuwono, Zeus Abdi; Palit, Herry Christian (Jurnal Titra, 2015)
Management at finished goods warehouse owned by PT. FSCM Manufacturing Indonesia is less effective. That problem makes the warehouse becomes disorganized. The suggested designs to improve warehouse management include optimizing the warehouse capacity, redesigning of the warehouse layout, and improving goods placement system. Additionally, measurement of warehouse performance makes warehouse management better. As the results, after the implementation of the new design, the warehouse is now well organized and itsperformance is improved.